(untitled) (International Seven Journal of Multidisciplinary, 2023)
The integration of digital technologies in dentistry has significantly transformed clinical practice, enhancing diagnostic accuracy, treatment planning, and patient outcomes. Innovations such as digital radiography, three-dimensional (3D) modeling, and 3D printing have enabled dental professionals to achieve greater precision, efficiency, and personalization in care. Digital radiography reduces radiation exposure and allows immediate image manipulation, improving diagnostic capabilities. 3D modeling with intraoral scanners and cone beam computed tomography facilitates accurate visualization of dental structures and supports customized treatment planning. 3D printing enables rapid fabrication of crowns, dentures, surgical guides, and orthodontic appliances with high precision and patient-specific customization. Collectively, these technologies optimize workflows, reduce clinical errors, and improve patient satisfaction, while ongoing advancements promise further enhancements in personalized, evidence-based dental care.